Musculoskeletal Injuries in Auto Racing: A Retrospective Study of 137 Drivers. Issue 4 (November 2014) - Koutras, Christos; Buecking, Benjamin; Jaeger, Marcus; Ruchholtz, Steffen; Heep, Hansjoerg
Abstract: Background and Purpose: The effect of continuous exposure of a driver's bones and muscles to vibration and G forces to years of automobile racing and the effect on overall health have not yet been examined in detail. The goal of this study was to investigate via questionnaire the musculoskeletal injuries and influencing parameters in 130 amateur and 7 professional race car drivers.Materials and Methods: A questionnaire, translated in English and German, was used to investigate the parameters that influence the racing performance and the character of resulting injuries.Results: This investigation involved 137 drivers (133 men and 4 women) with a mean age of 42 years (standard deviation = 15). Approximately half of the drivers had < 10 years of experience in auto racing (49%). The drivers mainly complained about pains in the lumbar (n = 36; 26%), shoulder (n = 27; 20%), and neck regions (n = 25; 18%). The driver's posture and the comfort of the seat were statistically significant for causing lower back and upper legs pains. The race duration was relevant to neck and shoulder discomfort.Conclusion: The high incidence of musculoskeletal injuries in race car driving indicates the need for further improvements. Elimination of driver complaints about pain in the spine and upper extremities can be achieved through technical development, as already accomplished in Formula One racing.